2015
DOI: 10.1017/s2045796015000281
|View full text |Cite
|
Sign up to set email alerts
|

Generating evidence to narrow the treatment gap for mental disorders in sub-Saharan Africa: rationale, overview and methods of AFFIRM

Abstract: There is limited evidence on the acceptability, feasibility and cost-effectiveness of task-sharing interventions to narrow the treatment gap for mental disorders in sub-Saharan Africa. The purpose of this article is to describe the rationale, aims and methods of the Africa Focus on Intervention Research for Mental health (AFFIRM) collaborative research hub. AFFIRM is investigating strategies for narrowing the treatment gap for mental disorders in sub-Saharan Africa in four areas. First, it is assessing the fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 17 publications
1
71
1
1
Order By: Relevance
“…Detailed information on the AFFIRM-SA trial and the development of the intervention is available elsewhere [11, 35, 36]. We approached a local Non-Governmental Organisation (NGO) which provided twelve CHWs to participate in the training.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed information on the AFFIRM-SA trial and the development of the intervention is available elsewhere [11, 35, 36]. We approached a local Non-Governmental Organisation (NGO) which provided twelve CHWs to participate in the training.…”
Section: Methodsmentioning
confidence: 99%
“…The authors demonstrated improved maternal and child health outcomes and established the potential for midwives and community health workers to successfully deliver basic mental health services . Additional evidence will also likely come from the Africa Focus on Intervention Research for Mental Health (AFFIRM) and the Programme for Improving Mental Health Care (PRIME), both multicountry initiatives in low‐ and middle‐income countries with sites in sub‐Saharan Africa that explore the impact of packages of care that integrate mental health services into primary care . Such packages of care are delivered in community settings by community health workers, including midwives, who are trained to identify individuals with mental disorders using locally developed and validated tools and provide manual‐based counseling, under the supervision of mental health specialists .…”
Section: Meeting the Need: Integration Of Mental Health Into Maternalmentioning
confidence: 99%
“…First of all, the implementation of an objective approach requires adequate policies and resources beginning with a genuine integration of the work of primary care providers and mental health professionals through the constitution of multidisciplinary, democratized teams open to the active participation of the patients themselves and their families (31,75,88). All of this entails respect for the human dignity and the cultural background of the individual patient and his/her surroundings, making it possible a comprehensive, realistic and pragmatic clinical management and reasonable outcome-oriented follow up (63,70,89).…”
Section: The Futurementioning
confidence: 99%